Expanding Middle Class in Indonesia - Devanto Shasta Pratomo; Wildan Syafitri; Clarissa Sekar Anindya (Pusbindiklatren Bappenas, 2020)
The Indonesian economy has been one of the promising economies, with an average annual economic growth of about 5% in the last decade. With income per capita US 4050 as of 2019, Indonesia is now moving to attain upper-middle-income country status. Indonesia escaped from the lower-middle-income trap that the country has faced since 1985 by improving its human capital through increased attention to education and reduction in poverty. Alongside a significant poverty reduction, the middle class or middle-income population has been significantly growing. According to the National Socio-Economic Survey (SUSENAS), the middle-class household grew from only 9% in 1993 to more than 20% in 2019. The middle class also works as an engine for growth, supporting nearly half of total national consumption. They are more likely of having better human capital, work as white-collar workers, and mostly living in urban areas. Due to the greater education and skills most of those in the middle class, have greater access to working in the formal sector jobs, and some are increasingly running productive business or entrepreneur which drives growth and creating jobs for others (World Bank, 2019).